Granulocyte Transfusion Therapy: Institutional Experience of Benefit in Cancer Patients with Prolonged Neutropenic Sepsis—A Retrospective Study - Shrivastava, Shiv Prasad; Elhence, Aditya; Jinwala, Prutha; Bansal, Shashank; Chitalkar, Prakash; Bhatnagar, Shweta; Patidar, Rajesh; Asati, Vikas; Reddy, Pradeep Kumar (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Patients undergoing intensive chemotherapy for hematological malignancy and stem cell transplantation are at increased risk of neutropenia.Neutropenia is among the frequent side effects of intensive treatments, and when absolute neutrophil count (ANC) falls < 500/µL, the risk of microbial and fungal infection increases significantly.As neutropenia is the main cause of these infections, transfusion of granulocyte immediately as a replacement is a life-saving therapeutic option to support these patients by restoring neutrophil counts and aiding in the resolution of infection.Objective The present study is a retrospective single institutional analysis of granulocyte transfusion therapy in children and young adults with cancer who received treatment with GT during prolonged and profound life threatening neutropenia.Materials and Methods This study was a retrospective analysis of 66 granulocyte transfusions in 36 patients of hematological and solid malignancy with severe and prolonged neutropenia in the department of Medical Oncology, Sri Aurobindo Institute of Medical Sciences Indore, between September 2019 and March 2022.Donors were either patients' relatives or voluntary donors without comorbidities.All granulocyte concentrates were collected by centrifugation leukapheresis and irradiated with 2500 centigray and immediately transfused in full, to the patient over 60 ot 120 minutes with appropriate premedication.Results A total of 36 patients (M:F, 19:17) with a median age of 16 years (2–43) received 66 granulocyte transfusions. The diagnosis of patients included acute myelogenous leukemia (n = 17), B cell acute lymphoblastic leukemia (n = 10), non-Hodgkin lymphoma (n = 3), Ewing's sarcoma (n = 2), neuroblastoma (n = 1), malignant melanoma (n = 1), aplastic anemia (n = 1), osteosarcoma (n = 1). All had severe neutropenia with absolute neutrophil count < 0.5 × 109/L. The median duration of severe neutropenia was 16 days. Patients received a median cell dose of granulocytes 2.9 × 1010/L. A favorable response was seen in 28 (78%) patients, whereas an unfavorable response was seen in 8 patients (23%).Conclusion A granulocyte therapy was effective in many critically sick patients with prolonged and profound neutropenia. Granulocyte transfusions may be more beneficial in selected patients where it provides more time to overcome refractory infections with broad-spectrum antibiotics. Granulocyte transfusion are at best a “bridge” that gives time to marrow recovery. The challenges to using GT are clinical, finding patients who may get benefitted, and logistical, selection of donors and harvest technique. Randomized trials with large numbers of patients are required to prepare guidelines for granulocyte use.
Keywords: cancer; granulocyte transfusion; neutropenia